Provision of oral healthcare services in WHO-EMR countries: a scoping review - Lamis Abuhaloob; Celine Tabche; Federica Amati; Salman Rawaf (BMC, 2024)
Abstract Global neglect of oral healthcare services (OHCS) provision, mainly in Low- and Middle-Income Countries, exacerbates the deterioration of health systems and increases global health inequality. Objectives The objective is to explore the profiles of available oral healthcare services in the WHO Eastern Mediterranean Region (EMR) countries. Methods A systematic literature search was conducted of grey literature and databases (PubMed, Medline, Embase, and the Cochrane Library). Peer-reviewed articles that reviewed and/or evaluated OHCS in WHO-EMR countries were identified. No time or language limitations were applied. Two independent reviewers conducted the screening and data extraction. A third reviewer arbitrated disagreement. The evaluation of the OHCS provision followed the WHO framework for health system performance assessment. The extraction included socio-demographic characteristics of the studied population, OHCS profile, responsiveness, and health insurance coverage. Results One hundred and thirty-seven studies were identified. The studies that met the inclusion criteria were fifteen published between 1987 and 2016. In addition, two reports were published in 2022. The included studies were conducted in Pakistan, Saudi Arabia, Iran, Libya, Egypt, Oman, Syria, Jourdan, Kuwait, and Tunisia. Generally, Ministries of Health are the main providers of OHCS. The provision for national dental care prevention programmes was highly limited. Furthermore, most of these Ministries of Health have struggled to meet their local populations' dental needs due to limited finances and resources for OHCS. Conclusions Oral and dental diseases are highly prevalent in the WHO-EMR region and the governments of the region face many challenges to meeting the OHCS needs of the population. Therefore, further studies to assess and re-design the OHCS in these countries to adapt dental care prevention into national health programmes are crucial.